Pengaruh Brand Image dan Brand Awareness terhadap Purchase Decision Produk iPhone melalui Word of Mouth - Aditya Cahya Nugraha; Heru Sulistyo (ARZUSIN, 2026)
The increasingly intense competition in the smartphone industry requires companies to strengthen brand-based marketing strategies to sustain consumer purchase interest, including among university students who use iPhone as a premium product segment. This study aimed to analyze the effect of brand image and brand awareness on purchase decisions for iPhone products, with word of mouth as an intervening variable. A quantitative approach was employed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires from 157 iPhone-using students at Universitas Islam Sultan Agung Semarang, selected using purposive sampling. The results show that brand image and brand awareness have a positive and significant effect on word of mouth. In addition, brand image and word of mouth have a positive and significant effect on purchase decisions, whereas brand awareness does not have a significant direct effect on purchase decisions but exerts an indirect effect through word of mouth. These findings highlight the important mediating role of word of mouth in strengthening the influence of brand image and brand awareness on purchase decisions. The implications suggest that companies need to reinforce strategies for building a positive brand image and encouraging conducive communication among consumers to enhance purchase decisions for iPhone products in the student segment.